Analisis Pemanfaatan Media Pembelajaran Daring Pada Masa Belajar Dari Rumah Di Sdn 02 Banyuurip Kabupaten Temanggung - Putri Nova Andianik; Iin Purnamasari; Intan Rahmawati (Jurnal Ilmiah Wahana Pendidikan, 2022)
Putri Nova Andianik. NPM 16120009. "Analysis of the Use of Online Learning Media During Studying from Home at SDN 02 Banyuurip, Temanggung Regency". Thesis for Elementary School Teacher Education Study Program Faculty of Education, PGRI University Semarang 2022. Indonesia is currently experiencing the Corona epidemic, which affects every human activity, including the world of education. The government recommends regulations for physical distancing. On the other hand, in order to keep the world of education running well and support the government in supporting physical distancing in the midst of the Covid-19 pandemic, according to the president's instructions to stay at home, study at home, work at home, worship at home. The increasing number of the spread of the corona virus in Indonesia has prompted the government to issue several policies or steps that can be taken during the corona virus pandemic, the policies carried out are intended to avoid the spread of the corona virus to students in various schools or colleges. Some of the policies taken are learning is done from home (Distance Learning). The focus of this research is "analysis of the use of online learning media during learning from home at SDN 02 Banyuurip, Temanggung Regency". With the formulation of the problem "how is the media used by the teacher in Distance Learning?" and "how is the effectiveness of the media used by teachers in Distance Learning?". The purpose of this study is to analyze the media used by teachers in Distance Learning and analyze the effectiveness of the use of media used by teachers in Distance Learning. The approach in this research is a qualitative approach. This type of research is descriptive research, which collects as much descriptive data as possible as outlined in reports and descriptions. This research was conducted at SDN 02 Banyuurip, Temanggung Regency in Semester 2 of the 2020/2021 Academic Year. Data collection techniques in this study were observation, interviews and documentation. The results of this study are the media used in online learning are whatsapp groups and youtube. The use of whatsapp groups and youtube is carried out in all classes. school, study from home, pandemic